2022
DOI: 10.1186/s40337-022-00719-2
|View full text |Cite
|
Sign up to set email alerts
|

“I’m not alone”: a qualitative report of experiences among parents of children with eating disorders attending virtual parent-led peer support groups

Abstract: Background The treatment for children with eating disorders (EDs) requires extensive involvement of parents. The parents of children with EDs have voiced a need for greater support, including connecting with other parents with lived experience of caring for a child with an ED. We aimed to qualitatively explore parental experiences of these groups, including their benefits and areas for improvement. Methods This study examined the delivery of four v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
0
9
0
1
Order By: Relevance
“…In addition, substantial work has been conducted in developing and evaluating carer support programs in face-to-face (e.g., Goddard et al, 2011) and online formats (e.g., Spencer et al, 2019), with one study finding comparable benefits across both (Truttmann et al, 2020). There is also evidence of parent-led support groups being rated as helpful with participants highly valuing the ability to connect with other parents who understood their experiences (Grennan et al, 2022). Some services already include skills-based workshops, and we need such programs to be more widely available.…”
Section: Expansion Of Effective Parent-support Options and Creating N...mentioning
confidence: 99%
“…In addition, substantial work has been conducted in developing and evaluating carer support programs in face-to-face (e.g., Goddard et al, 2011) and online formats (e.g., Spencer et al, 2019), with one study finding comparable benefits across both (Truttmann et al, 2020). There is also evidence of parent-led support groups being rated as helpful with participants highly valuing the ability to connect with other parents who understood their experiences (Grennan et al, 2022). Some services already include skills-based workshops, and we need such programs to be more widely available.…”
Section: Expansion Of Effective Parent-support Options and Creating N...mentioning
confidence: 99%
“…Although qualitative research has explored participant experiences of peer support groups for parents of children with EDs (Grennan et al, 2022;Oakley et al, 2021), this is the first study to demonstrate that vPLPSGs are a feasible intervention, associated with strong acceptability and promising preliminary effectiveness for this parent population.…”
Section: Discussionmentioning
confidence: 99%
“…In response to this gap in research, we implemented several virtual parent-led peer support groups for parents of children with EDs living in Ontario, Canada over a year-long period. A qualitative paper arising out of this work found that the exposure to and support from parents in similar scenarios was valuable for parents (Grennan et al, 2022). Participants provided various recommendations for future implementation of this intervention, including greater specificity when allocating parents to groups (e.g., grouping participants based on child's ED type, duration of ED, or geographical location).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, carers of children with anorexia nervosa, particularly mothers, also reported feeling a strong sense of loneliness. Therapists could consider directing carers to peer support to help reduce feelings of isolation and loneliness (Binford Hopf et al, 2013; Grennan et al, 2022). It is important to note, however, that the current results are correlational in nature, and further research is needed to determine optimal procedures of intervention for addressing illness representations.…”
Section: Discussionmentioning
confidence: 99%